GE_GERICHTE P/22594/2016 vom 25. Mai 2020 - GE Cour de justice (2020)
CLASSEMENT DE LA PROCÉDURE;PLAINTE PÉNALE;PERSONNE PROCHE;GESTION DÉLOYALE;ESCROQUERIE;GÉRANT(SENS GÉNÉRAL);TROMPERIE;CRÉDIT HYPOTHÉCAIRE;AFFAIRE CIVILE | CPP.319.al1; CP.30; CP.31; CP.158; CP.146